The effectiveness of ARCS embedded Computer Assisted Learning materials in supporting an integrated approach to teaching English grammar / Nor Syahiza Shahabani - Shahabani, Nor Syahiza (2007)
Learning and teaching English effectively still remains an issue in an L2 environment. Effective teaching approaches coupled with CAL materials can enhance students" learning motivation and interest. Despite the advantages of using electronic teaching media, many teachers still hesitate to use them. The purpose of the study was to investigate the effectiveness of using CAL materials in teaching English grammar. The hypotheses were to investigate if there is/are (1) a significant difference in the English grammar performances between the students learning via a technology supported integrated approach and those learning through a "chalk and talk" approach; (2) a significant difference in the English grammar performances between gender when using CAL materials. A research question was also posed to examine how learners rate the ARCS embedded CAL materials used in the learning of English grammar. Sixty randomly selected Form 1 secondary school students from SMK Bandar Tasik Puteri, Rawang. Selangor, participated in the study. The experimental group (n=30) was exposed to the research treatments; while, the control group (n=30) went through the learning via the traditional teaching using 'calk and talk' approach. The selected subjects were of the same English level competency. Two instruments were used to solicit students" English grammar performances and their responses towards CAL materials using the ARCS model. Paired Sample T-Tests analyzing variations between groups and pre-post tests were conducted. The analyses reported (a) a significant difference (p=.001) between the performance of the experimental group students when compared to the control group students in the English grammar (tenses) posttest; (b) a significant difference (p=.000) between the performance of the experimental group students before and after they underwent their learning experiences using CAL materials; (c) no significant difference (p=. 194) between the posttest performances of the experimental group students based on gender differences. Students' responses on ARCS components revealed mostly positive responses on all test items. The use of CAL materials in classroom activities has improved students' performances. Both genders benefit from using CAL materials in their learning experiences. The stereotype assumption about male dominance in technology is not visible in this study. CAL materials selected are those that can capture learners' attention, relevant to the learners' experiences, can increase learners' motivation and can give satisfaction to the learners. Finally, understanding students' learning motivation is essential as it determines the quality of the students' academic accomplishment. In the teaching English grammar, this motivation can lead to students' mastering of the English grammar concepts, rules and structures.